THE INFLUENCE OF SERVICE QUALITY ON PATIENT SATISFACTION AT HATI KUDUS LANGGUR HOSPITAL - Yessi Virginia Lasol; Maria Widyarini; Kevin Grahadian (LPPM STIE Muhammadiah Bandung, 2025)
This study explores the relationship between the quality of healthcare services and patient satisfaction at Hati Kudus Langgur Hospital. The main aim is to assess whether service quality has a significant impact on how satisfied patients are with the hospital's services. A quantitative method is utilized, using a structured questionnaire to collect data. The research targets all patients of the hospital, with a sample size of at least 123 respondents, calculated using the Slovin formula. The analysis methods include descriptive statistics, simple linear regression, validity and reliability tests, as well as the coefficient of determination (R²). The findings indicate: (1) Tangibility has a significant positive influence on patient satisfaction; (2) Reliability does not significantly influence satisfaction; (3) Responsiveness has a meaningful effect on satisfaction; (4) Assurance significantly contributes to satisfaction; and (5) Empathy does not show a significant impact on patient satisfaction at the hospital.